Evaluasi Kebijakan Perlindungan Konsumen dalam Transaksi Digital di Indonesia: Studi Kebijakan dan Analisis SWOT - Kharisma, Dian; Tobing, Wesly Tumbur ML; Susanti, Eni; Aprili, Ronaldo (Universitas Sains dan Teknologi Komputer, 2024)
The rapid growth of digital transactions in Indonesia has significantly transformed consumer behavior and the economic landscape. Despite this progress, various challenges, particularly in consumer protection, remain unresolved. Current regulations, including the Consumer Protection Law (UUPK) and the Information and Electronic Transactions Law (UU ITE), provide a foundational legal framework, yet their implementation has been inconsistent and often ineffective. This research aims to evaluate the policies governing consumer protection in digital transactions and identify strategies for improvement. A qualitative approach, utilizing SWOT analysis, was employed to examine the strengths, weaknesses, opportunities, and threats within the existing framework. Data were gathered from in-depth interviews with stakeholders and analysis of relevant legal and policy documents. The findings reveal significant gaps in consumer literacy, ineffective dispute resolution mechanisms, and insufficient adoption of advanced technologies like blockchain. However, the rapid growth of the digital economy and initiatives such as